The body under the piano - Jocelyn, Marthe; Follath, Isabelle ([Plattsburgh, NY] : Tundra, 2020)
"Aggie Morton lives in a small town on the coast of England in 1902. Adventurous and imaginative but deeply shy, Aggie hasn't got much to do since the death of her beloved father...until the fateful day when she crosses paths with twelve-year-old Belgian immigrant Hector Perot and discovers a dead body on the floor of the Mermaid Dance Room! As the number of suspects grows and the murder threatens to tear the town apart, Aggie and her new friend will need every tool at their disposal--including their insatiable curiosity, deductive skills and not a little help from their friends--to solve the case before Aggie's beloved dance instructor is charged with a crime Aggie is sure she didn't commit"--Provided by the publisher.
"Inspired by the real-life Queen of Crime, Agatha Christie"--Cover.
Junior Library Guild
Ages 10-13.
Grades 5-8.
750L
A Junior Library Guild selection
Keywords: Mystery and detective stories; England -- Fiction